Pengaruh Kepemimpinan Berbasis Nilai-Nilai Islam Dalam Efektivitas Manajemen Komunikasi Organisasi - Dwi sumawati; Itsna Nuzulla; Ismail Mubarok (Student Research Journal, 2023)
Leadership based on Islamic values is a type of leadership that is based on Islamic values such as morality, justice, consideration, and honesty. Organizational communication isimportant to achieve organizational goals effectively and efficiently. Organizational communication management involves planning, organizing, implementing, and monitoring all communication channels within an organization. The methoud used is qualitative method. Qualitative methods are methods that focus ondetailed observations of the impact of leadership based on Islamic values on the effectiveness of organizational communication management, which can have a positive and important impact on Islamic organizational culture. Emphasis on justice, honesty, loyalty, and responsibility are the pillars of Islamic leadership. The main aspects and theories of leadership in islam include several aspects that provide a foundation for leadersto guide and motivate members of organizational. This research aims to investigate the influence of leadership based on Islamic values on the effectiveness of communication management in an organization. The research method used was a survey of employees from several organizations in Indonesia. The research results show that leadership based on Islamic values has a significant influence on the effectiveness of organizational communication management. Leaders who integrate Islamic principles in their leadership are able to create an inclusive work environment, increase trust, and facilitate the effective flow of information. This research provides a better understanding of the importance of Islamic values in strengthening the relationship between leadership and communication management in an organizational context.